2003
DOI: 10.1645/ge-60r
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Isolates of Free-Ranging Chickens From Rio de Janeiro, Brazil: Mouse Mortality, Genotype, and Oocyst Shedding by Cats

Abstract: Most isolates of Toxoplasma gondii can be grouped into 3 genetic lineages. In the present study, 67 isolates of T. gondii were obtained by bioassay in mice inoculated with brains and hearts of 96 asymptomatic chickens from an area highly endemic to human infection in Rio de Janeiro, Brazil. Of the 48 isolates genotyped using the SAG2 locus, 34 (70%) were of type I and 13 (27%) were of type III. No isolate of type II was recovered. Isolates from 1 chicken contained a type I and type III mixed infection, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 33 publications
(19 reference statements)
4
39
0
4
Order By: Relevance
“…Three virulent strains (CH4, CH5 and CH10) in mice were type I and one (CH11) was type I or II. Our results are in agreement with those by Dubey et al (2002Dubey et al ( , 2003a, who observed a predominance of T. gondii isolates as being type I in chickens obtained in the States of São Paulo and Rio de Janeiro. On the other hand, other reports have revealed that T. gondii isolates from chickens obtained in Argentina (Dubey et al, 2003c), Egypt (Dubey et al, 2003d) and the US (Dubey et al, 2003e) were mostly type III, suggesting a different epidemiological prevalence of T. gondii genotypes in Brazil, as compared to other countries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Three virulent strains (CH4, CH5 and CH10) in mice were type I and one (CH11) was type I or II. Our results are in agreement with those by Dubey et al (2002Dubey et al ( , 2003a, who observed a predominance of T. gondii isolates as being type I in chickens obtained in the States of São Paulo and Rio de Janeiro. On the other hand, other reports have revealed that T. gondii isolates from chickens obtained in Argentina (Dubey et al, 2003c), Egypt (Dubey et al, 2003d) and the US (Dubey et al, 2003e) were mostly type III, suggesting a different epidemiological prevalence of T. gondii genotypes in Brazil, as compared to other countries.…”
Section: Discussionsupporting
confidence: 93%
“…Howe et al (1997) developed a typing system for T. gondii strains based on analysis of restriction fragments of the gene SAG2, amplified by nested-PCR, which allows a differentiation among strain genotypes of the three clonal lineages, previously described by Howe & Sibley (1995). In Brazil, this method was used for analyzing T. gondii isolates from São Paulo (Dubey et al, 2002), Rio de Janeiro (Dubey et al, 2003a) and Paraná (Dubey et al, 2003b), which showed to be predominantly type I. Ferreira et al (2006), using a multilocus PCR-RFLP, demonstrated that Brazilian strains present recombinant genotypes with typical alleles of the strains types I, II, and III in the majority of the loci.…”
Section: Introductionmentioning
confidence: 99%
“…However, such meats are under sanitary control, and hence, neosporosis and toxoplasmosis from these sources were not investigated in the present survey. The seroprevalence of T. gondii among chickens in Brazil ranges from 39% to 66% (DA SILVA et al, 2003;DUBEY et al, 2003;DUBEY et al, 2006;DE OLIVEIRA et al, 2009); and among cattle, from 1% (GONDIM et al, 1999) to 71% (SANTOS et al, 2009). On the other hand, the seroprevalence of N. caninum among cattle in Brazil ranges from 14.3% (GUIMARÃES et al, 2004) to 91.2% (GUEDES et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos de prevalência do T. gondii em fazendas de ovinos com manejo intensivo no Reino Unido ressaltam a importância da transmissão congênita e relatam que o risco de outras vias de infecção é reduzido, podendo ser a transmissão congênita suficiente para explicar a manutenção do agente nessas populações (ENGELAND et al, 1996;DUNCANSON et al, 2001 Brasil em outras espécies animais como em cães , galinhas DUBEY et al, 2003d;;DUBEY et al, 2003e), gatos (DUBEY et al, 2003;PENA et al, 2006), suínos (SANTOS et al, 2005, SOUSA et al, 2006 MONDRAGON et al,1998;FUENTES et al, 2001;ASPINALL et al, 2003). Os isolados tipo I têm se apresentando virulentos a camundongos com alta parasitemia quando comparados com os outros genótipos e com uma possível correlação com infecção congênita em humanos.…”
Section: -Discussãounclassified
“…Os isolados tipo I têm se apresentando virulentos a camundongos com alta parasitemia quando comparados com os outros genótipos e com uma possível correlação com infecção congênita em humanos. Isolados tipo II foram os mais prevalentes tanto em humanos como em animais em várias partes do mundo, havendo uma possível correlação com reativação da toxoplasmose em indivíduos imunocomprometidos (HOWE et al, 1997;MONDRAGON et al,1998;FUENTES et al, 2001 , DUBEY et al, 2003d, DUBEY et al, 2003e, DUBEY et al, 2006FERREIRA et al, 2006, DUBEY et al 2007). Outras espécies animais estudadas no Brasil, também apresentaram perfil semelhante , SANTOS et al, 2005, YAI, et al, 2006 Utilizando métodos moleculares com maior resolução, é observada a ocorrência de padrões recombinantes ou atípicos entre as amostras brasileiras (CAVALCANTE et al, 2006b;DUBEY et al 2007;DUBEY et al, 2007a).…”
Section: -Discussãounclassified